Decaying Lava Extrusion Rate at El Reventador Volcano, Ecuador, Measured Using High‐Resolution Satellite Radar. Issue 12 (29th December 2017) - Arnold, D. W. D.; Biggs, J.; Anderson, K.; Vallejo Vargas, S.; Wadge, G.; Ebmeier, S. K.; Naranjo, M. F.; Mothes, P.
Abstract: Lava extrusion at erupting volcanoes causes rapid changes in topography and morphology on the order of tens or even hundreds of meters. Satellite radar provides a method for measuring changes in topographic height over a given time period to an accuracy of meters, either by measuring the width of radar shadow cast by steep sided features, or by measuring the difference in radar phase between two sensors separated in space. We measure height changes, and hence estimate extruded lava volume flux, at El Reventador, Ecuador, between 2011 and 2016, using data from the RADARSAT‐2 and TanDEM‐X satellite missions. We find that 39 new lava flows were extruded between 9 February 2012 and 24 August 2016, with a cumulative volume of 44.8M m 3 dense rock equivalent and a gradually decreasing eruption rate. The average dense rock rate of lava extrusion during this time is 0.31 ± 0.02 m 3 s −1, which is similar to the long‐term average from 1972 to 2016. Apart from a volumetrically small dyke opening event between 9 March and 10 June 2012, lava extrusion at El Reventador is not accompanied by any significant magmatic ground deformation. We use a simple physics‐based model to estimate that the volume of the magma reservoir under El Reventador is greater than 3 km 3 . Our lava extrusion data can be equally well fit by models representing a closed reservoir depressurising during the eruption with no magma recharge, or an open reservoir with a time‐constant magma recharge rate of up to 0.35 ± 0.01 m 3 s −1 . Key Points: High‐resolution satellite radar measures extruded lava volume at the andesitic El Reventador stratovolcano at 11 day to 10 month intervals The time‐averaged lava extrusion rate decays gradually over the 4 year observation period We fit the extrusion rate with a model of a depressurising reservoir, with constant magma influx from below at rates less than 0.35 m 3 s −1